THE STUDY OF THE ANTECEDENTS OF RETAIL SHOPPERS’ REPATRONAGE INTENTIONS: AN EMPIRICAL STUDY - Budi Hartono Kusuma, Andreas Widjaja, (Jurnal Ekonomi, 2015)
One of important factors that determine the success of retail stores is how to make customers go to shop there, in which they have to shop there continuously. So, retailers should   have to satisfy customers in order to keep customers. In this research, the researcher would like to test and describe customer satisfaction and repatronage  intentions, through eight  variables in Carrefour and Hypermart, and developed into seven hypotheses. This research uses 160 samples to ask their perceptions about Carrefour and Hypermart. Then, from that research, there are two hypotheses that are  rejected and five hypotheses  that  are  accepted.  Perceived product  quality  and perceived price are considered as insignificant antecedents of customer satisfaction. However, perceived service quality, store assortment, trust and commitment are considered as significant antecedents   of   customers’ satisfaction, and customer satisfaction is significant antecedent of repatronage intentions.